Isolation, Purification and Identification of Active Chemical Compound Lup-20(29)-ene-3, 28-diol (Betulin) from Tetradium daniellii Leaves and Study the hypoglycemic Effect on Rabbits - Harbi Hussien Alsaadi, Jamal (University of Thi-Qar Journal of Science, 2019)
Diabetes mellitus is a syndrome and serious complex chronic condition leading to higher blood glucose levels that is a major source of health disorder worldwide, about 171 million or more diabetes mellitus cases worldwide in patients ages 20 years or more. The active chemicals compounds that isolated from medicinal plants were used succifully to treat this disease .the current study was extracted and isolated the bioactive compound (Lup-20(29)-ene-3, 28- diol ) from (Tetradium daniellii ) leaves. Were isolated, separated, purified and identified by thin layer chromatography, column chromatography, gas chromatography, IR-spectroscopy, 1H-NMR,C13-NMR,dept-NMR, Gas chromatography – mass spectroscopy. Also study of hypoglycemic action in blood glucose levels in normalglycemic and alloxan induced diabetic rabbits of Lup-20(29)-ene-3, 28-diol compound, a significant decreasing (P<0.01) at fourth and sixth hrs , and high significant decreasing (P<0.001) at twenty forth hrs. in hyperglycemic rabbits ,while in no rmalglycaemic rabbits, a significant decline (P<0.05) was at sixth , and a high significant decreasing ( P<0.01) was recorded at twenty forth hrs.